On the Wiener–Hopf factorization of rational matrices - Vakhtang Lomadze (Transactions of A. Razmadze Mathematical Institute, 2018)
The Wiener–Hopf factorization theorem for rational matrices is proved with respect to very general contours using purely algebraic method. Keywords: Rational functions, Matrices, Modules, Vector bundles, Cohomologies